Supporting Factors the Achievement of Work-Life Balance in Employees: a Systematic Review - Irfani, Alfina Diana; Triyuliasari, Anisah (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Work-life balance is an individual's ability to manage work and non-work life. This research aims to analyze 17 national and international journals on factors that support the achievement of work-life balance. The study employs a systematic review method, which involves identifying, selecting, and critically analyzing relevant academic literature to extract key insights. Journals were selected based on their relevance to work-life balance themes and their publication within the last decade. The results of the systematic review indicate that factors that support the achievement of work-life balance for employees are divided into four major factors. (1) Individual factors such as time and stress management skills, employee resilience. (2) Organizational factors include the provision of childcare center facilities, the implementation of flexible work hours and places policies, the provision of work method policies, the provision of facilities that support performance, the provision of social support in the organization, and the implementation of organizational culture. (3) Environmental factors that include family such as family support and division of household chores. (4) Other factors that can be in the form of government policies and laws to protect employees. The results of this study can be a guideline for organizations and employees to improve work-life balance.